Financing Private Universities in a Time of Declining Enrolments in Ghana - Richard Lionel Gorni; Eka Prihatin; Asep Suryana (Image : Jurnal Riset Manajemen, 2025)
Ghana's private universities, essential to the nation's educational landscape, are grappling with financial challenges due to declining enrollment and rising educational costs. This confluence threatens the sustainability of these institutions, despite their vital role in expanding access to higher education. This paper examines the financial strains on private universities in Ghana. By analyzing existing research and data on educational costs and enrollment trends, the paper identifies key factors contributing to financial instability. High educational costs pose a significant barrier for many students, potentially limiting their ability to pursue higher education at private institutions. Universities also face financial constraints, struggling with limited resources to maintain quality education and infrastructure. The paper goes beyond problem identification to propose solutions through a two-pronged approach: internal university efforts and external support. Internally, universities can implement cost-containment measures to streamline operations and enhance financial efficiency. Additionally, developing innovative programs that meet current market demands can attract new students and generate revenue. Externally, government support and policy reforms are crucial for sustainability. Financial aid programs, tax breaks, and other supports can alleviate some financial burdens. Policy reforms addressing affordability and student loan options can make private universities more accessible, broadening their reach and impact.